Caracterização das unidades máfica-ultramáficas e potencial metalogenético da sequência metavulcanossedimentar Serra das Pipocas (Ceará): um provável Greenstone Belts - Sousa, Herdivânia Pires de (2016)
The Rhyacian Serra das Pipocas Greenstone Belt, is part of Archean/Proterozoic terrene of Ceará Central Domain, in the Setentrional portion of Borborema Province. It is located in Southwestern Ceará, between the municipalities of Boa Viagem, Independência, Tauá and Pedra Branca. Geological mapping techniques, thin and polished sections petrography, mineral chemistry, lithogeochemistry, and geochronology have been useful in the distinction of the first Greenstone Belt sequence in Ceará. The metavolcanic-sedimentary sequence is composed of metasedimentary rocks, marly psammite-pelite, containing alternation of mafic-ultramafic volcanic floods, tholeiitic and komatiitic, respectively, and meta-acidic rocks. The komatiitic meta-ultramafic floods are composed of chlorite-anthophyllite-actinolite-tremolite schist displaying acicular texture, or not, occuring discontinuously near the bottom of the sequence. The tholeiitic metamafic rocks are mainly represented by garnet amphibolites, which continuously extend 30km in length by 500m – 1km wide. Basic and acidic metatuffs, metacherts, and banded iron formation are alternated with amphibolites, which sometimes are deeply hydrotermalized. Metasedimentary rocks are mainly terrigenous, containing biotite, kyanite; however, occasional centimetric alternation of calc-silicatic rocks are observed. These lithotypes are cutted off by mafic-ultramafic intrusions, metagranodiorites and metabasic dykes. The lithological association has been developed in a extensional enviroment, probably a back-arc basin, where the komatiitic rocks Mg-Bearing schists display a transition from Munro-type to Barbeton-type, while the tholeiitic metabasalts (amphibolites) are iron-magnesium-rich. Regarding the structural geology, the area is caracterized by penetrative polyphasic strain, occurred during Brasiliano, with tight, isoclinal and recumbent folds, in addition to thrust faults and shear zones. The thrust faults are best recognized, especially, in the contact between the metavolcanic-sedimentary sequence and granite-gneiss-migmatite of Cruzeta Complex; also, between the mafic-ultramafic subunits. The metamorphic grade of the lithological association varies from high greenschist facies to high amphibolite facies, contrasting with Cruzeta Complex units, which are frequently migmatized. Besides, during the Brasiliano orogenesis, leucocratic granites have been intruded along the border zones of the oldest granites (2181,4±4.4), near the Queimadas thrust fault, there are deeply hydrotemalized rocks, displaying silicification, potassification, chloritization, and carbonation, sulphidation is also present, and they may contain some mineralisation such as copper-gold Volcanic-hosted Massive Sulfide or auriferous lodes, because this association occurs near the silicified zones and also in shear zones.